MEMBINGKAI HOLISTIC EDUCATION DAN NILAI-NILAI INSTITUSI BAGI TERWUJUDNYA REVOLUSI MENTAL: KAJIAN KONTRIBUSI PEMIMPIN PENDIDIKAN MELALUI PEMBERDAYAAN NILAI-NILAI INSTITUSI - Munifah FNU (Sekolah TinggiAgama Islam Negeri (STAIN) Kediri, 2016)
The paper highlights professional education management to empower environmental and spiritual values as a source of learning and to improve communication and collaboration in o r der to enhance mental revolution. As leaders of educational institutions, school principal is required to be more serious in realizing the intensity, extensity, clarity value on maximum quality. Teachers as agents of a mental revolution sho u ld improve their competence especially in translating the curriculum in the learning activities so that they are varied, fun, democratic, and meaningful so as to build the personality and behavior of students. Commitment and cooperation between the principal, the teachers, the community, and the government in est a blishing noble values will accelerate Indonesia civilized nations as expected by the movement of a mental revolution.